Modeling Infant i's Look on Trial t: Race-Face Preference Depends on i's Looking Style - Thomas, Hoben; Fassbender, Ina (Frontiers in Psychology, 2017)
\begin{abstract} When employing {\it between-infant} designs young infants' looking style (LS) is related to their development: Short looking (SL) infants are cognitively accelerated over their long looking (LL) peers. In fact, LS is a {\it within-infant} variable, and depends on infant $i$'s look distribution over trials. For the paired array setting, a model is provided which specifies the probability, $π_i\in [0,1]$, that $i$ is SL. The model is employed in a face preference study; 74 Caucasian infants were longitudinally assessed at 3, 6 and 9 months. Each $i$ viewed same race (Caucasian) versus other race (African) faces. Infants become SL with development, but there are huge individual differences in rate of change over age. Three month LL infants, $\hatπ_{i}<1/2$, preferred other race faces. SL infants, $\hatπ_{i}>1/2$, preferring same race faces at 3, and other race faces at 6 and 9 months. LS changes precede and may control changes in face preference. Ignoring LS can be misleading: Without considering LS, three month infants show no face preference. \end{abstract}